Local government policy to facilitate healthy and sustainable diets and the broader policy hierarchy: insights from Milan Urban Food Policy Pact cities - Liza R. Barbour; Julie L. Woods; Julie K. Brimblecombe (BMC, 2023)
Abstract Background Local government authorities are well positioned to change the way food is produced and consumed through the implementation of integrated food policies. By facilitating the uptake of healthy and sustainable diet-related practices, integrated local government food policy can trigger change throughout the food supply chain. This study aimed to provide insights as to how the policy hierarchy surrounding local governments may be influencing local government's capacity to create integrated food policy. Methods Content analysis was conducted on local government food policies (n = 36) from signatory cities of the Milan Urban Food Policy Pact were mapped to seven global regions. A set of 13 predetermined healthy and sustainable diet-related practices, organized into three categories: "where to source food", "what to eat" and "how to eat", was used to assess the level of integration of each local government food policy. Additional policies from the broader policy hierarchy that were mentioned in each local government food policy were sourced and then screened for relevancy, charted according to their level of administration (local, national, global region, international) and analysed to consider which diet-related practice(s) each broader policy was likely to promote. Results Analysis revealed three key insights: (i) local government food policies across all included global regions (n = 4) mostly promoted practices in the "where to source food" category, (ii) local government food policies across all global regions referred to policies from higher levels of administration (local, national, global region and international) which tended to also promote practices in the "where to source food" category and (iii) regarding the level of integration, local government food policies in Europe and Central Asia targeted the highest number of diet-related practices. Conclusions The level of integration of food policy at national, global region and international levels may be influencing that of local governments. Further research is required to understand why local government food policies are referring to some relevant policies and not others, and to determine whether a greater focus on the diet-related practices of "what to eat" and "how to eat" in policies from higher levels of government would support local governments to also prioritize these practices in their food policies.